Optimal electro-osmotic pumping of a micro-duct with finned structures. (February 2017) - Kung, Chun-Fei; Chang, Chien-Cheng; Wang, Chang-Yi
Highlights: Optimize EO pumping of a micro-duct with finned structures. Introduce a mathematical model that explains EO pumping rates. Provide diagrams of optimal EO pumping rates for practical design. Abstract: This article is aimed to present an analytic study of electro-osmotic (EO) pumping of a micro-duct with inserted fin vanes. Finned structures are known to be an efficient and very important tool in conducting heat generated in fluid transport system, such as Joule's heating in micro-fluidic devices. The present semi-analytical analysis is performed under the Debye–Hückel approximation (DHA), enabling us to explicitly investigate the combined effects of various parameters for optimizing the EO pumping rate while retaining substantial fin vanes for heat removal. A mathematical model based on the solutions of two fundamental EO flows is introduced to explain how the choice of the fin vane width may optimize the EO pumping rate in the general case. Moreover, we present the optimized EO flow rates in diagrams plotted on the plane of zeta potentials, which may serve as an easily used reference for engineering design and applications.